European Defense Economics - Kozelka, Josef; Sršeň, Radim; Dubský, Zbyněk, 1974-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2013)
The current economic crisis has led the leaders of the European states to decrease their spending on defense. This paper argues that if this reduction in public spending is not offset by the increase in international cooperation than the military capability of the region is going to deteriorate in the near future. The argument that the defense budgets are decreasing is based on the analysis of the data available for the public defense expenditures. Further six case studies of EU states are presented showing that the potential decrease in capability is observable in a wide range of EU countries. The case for greater international cooperation is based on the economic theory of comparative advantage and benefits of competition in the defense market. Furthermore, academic literature supporting this hypothesis is also presented to the reader throughout the paper. The conclusion of this paper is that the current tendency of governmental politicians of EU countries to ignore the need for greater international cooperation in the defense sector is unsustainable and that if European Union wants to maintain its position as one of the world power blocks, systematic reform of the EU defense market will need to be introduced.
Vedoucí práce: Radim Sršeň
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses